2019
DOI: 10.17305/bjbms.2019.4344
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells from bone marrow regulate invasion and drug resistance of multiple myeloma cells by secreting chemokine CXCL13

Abstract: Multiple myeloma (MM) is a hematologic cancer arising from plasma cells. Mesenchymal stem cells (MSCs) are a heterogeneous cell population in the bone marrow microenvironment. In this study, we evaluated the regulatory effects of MSCs on the invasion and drug resistance of MM cells U266 and LP-1. Bone marrow samples from MM patients and normal subjects were collected. MSCs were extracted from bone marrow and cultured, and their phenotypes were identified by flow cytometry. The level of CXCL13 in the supernatan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Studies have shown that inhibition of NF-κBc-Rel attenuates regulatory T cell-mediated immunosuppression and enhances the therapeutic efficacy of anti-PD-1 (Grinberg-Bleyer et al, 2017). Of the seven immune-related genes, three genes are associated with NF-κB activity (Deng et al, 2000;Kermarrec et al, 2019;Zhang et al, 2019). Therefore, it is further shown that the signature was associated with the response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that inhibition of NF-κBc-Rel attenuates regulatory T cell-mediated immunosuppression and enhances the therapeutic efficacy of anti-PD-1 (Grinberg-Bleyer et al, 2017). Of the seven immune-related genes, three genes are associated with NF-κB activity (Deng et al, 2000;Kermarrec et al, 2019;Zhang et al, 2019). Therefore, it is further shown that the signature was associated with the response to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in chronic lymphoid leukemia (CLL), forodesine-induced CLL cell apoptosis was antagonized by MSCs, which inhibited forodesine-induced RNA and protein synthesis activity and increased the expression of the antiapoptotic protein Mcl-1 at both the transcript and protein levels [ 88 ]. Moreover, in multiple myeloma (MM), it was found that MSCs enhanced MM cell resistance to bortezomib through CXCL13 production [ 89 ]. In solid tumors, MSCs have also been shown to promote resistance to therapeutic therapy.…”
Section: Mscs In Anticancer Therapeutic Resistancementioning
confidence: 99%
“…C‐C chemokine receptor type 2, which is activated by several chemokines, including MCP‐2, is known to polarize macrophages toward the M2‐like phenotype associated with drug resistance in MM 39 . It has been reported that resistance of MM cell lines to bortezomib was enhanced by mesenchymal stem cells through CXCL13 (BCA‐1) secretion 40 …”
Section: Discussionmentioning
confidence: 99%
“…39 It has been reported that resistance of MM cell lines to bortezomib was enhanced by mesenchymal stem cells through CXCL13 (BCA-1) secretion. 40 Serious toxicity can preclude optimum treatment and indirectly adversely impact on outcome. Our preliminary results indicate the potential to predict neurotoxicity using MIP-1α levels and thus stop treatment before potentially irreversible neurological damage.…”
Section: Protein Biomarkers Correlating With Treatment Response Tumor...mentioning
confidence: 99%